GRP-083 Hospital Pharmacists Can Improve Pharmacovigilance in the Emergency Room. (12th March 2013) - Aliberti, FA; Ciociano, N; Grisi, L; Elberti, MG; Alfieri, M; Lombardi, GM; Romano, F
Abstract : Background: Hospital pharmacists can play an important role in reporting adverse drug reaction (ADRs). Several publications underscore the fact that adverse drug events account for a substantial percentage of all hospital admissions. In the literature, several ways are mentioned in which the pharmacist can contribute to the safe use of drugs. Purpose: To establish ADRs in the Emergency Room (ER). Materials and Methods: This study was conducted from April 2010 to December 2011 in Salerno University Hospital. ADR report forms completed in the first 20 months of the project were analysed. Some of their key principles were collected: sex; suspected drug that caused the reaction and other drugs taken in association; description of ADRs and their classification as non-severe, severe or life-threatening. They were compared with ADR data for 2009. Results: 158 forms were analysed, each related to one different patient: 98 patients were women (68%). 50% of the events were connected with antibiotics, e.g. amoxicillin/clavulanic acid (28 cases), penicillin (19 cases), cephalosporins (17 cases); 35% concerned anti-inflammatories such as nimesulide (21%), propionic acid derivatives (21%), acetylsalicylic acid (14%), ketorolac (11%), steroidal anti-inflammatories (7%). 103 patients didn't take other drugs, but 55 had taken another one. Skin reactions were 52% of events, while 14% were cardiovascular events, 13% gastrointestinal problems, and 8% were respiratory reactions. Non-severe ADRs were 75%; 25% were severe and 1 case life-threatening. Before the project, in 2009 only one ADR had been reported; zero reports in the period January–March 2010. Conclusions: It is evident that the presence of a hospital pharmacist in ER increases the number of ADR reports: data confirms that a pharmacist who supports medical staff in reporting ADRs should be operative in all hospital departments. No conflict of interest.